Media Multitasking As Perception Strategy - Rankov, Pavol (Communication Today, 2025)
Information society has given rise to information explosion which is manifested by information overlap insi-de a medium or a programme (e. g. bricolage of picture, sound and unrelated crawling text in television news, or web links as permanent invitation to multitasking). A human requires immediate access to information as well as society requires immediate response from the human. Both of these tendencies are promoters of multitasking as information strategy. Conditions for multitasking are intra-personal and socio-cultural (e. g. neurotism and a highly television-oriented household). Several studies have shown that human brain isn´t adapted for simulnateous perception of different information. Heavy media multitaskers demonstrate their problems to concentrate on signiﬁcant stimuli, because they have developed a habit of treating all of the information with equal attention. Multitasking may become the key communication skill for the 21st century. This is challenge for media production as well as media education. The study gives overview on media multitasking.